2011
DOI: 10.1051/0004-6361/201116799
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship of shock waves to flares and coronal mass ejections

Abstract: Context. Metric type II bursts are the most direct diagnostic of shock waves in the solar corona. Aims. There are two main competing views about the origin of coronal shocks: that they originate in either blast waves ignited by the pressure pulse of a flare or piston-driven shocks due to coronal mass ejections (CMEs). We studied three well-observed type II bursts in an attempt to place tighter constraints on their origins. Methods. The type II bursts were observed by the ARTEMIS radio spectrograph and imaged b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 62 publications
2
40
0
5
Order By: Relevance
“…It is, in general, accepted that type II bursts at decametric and longer wavelengths are driven by CMEs, bow or flank (Vršnak and Cliver, 2008). At the metric range, on the other hand, they might be also due, apart from CMEs, to flare blasts (Cane and Reames, 1988;Nindos et al, 2011;Magdalenić et al, 2010Magdalenić et al, , 2012 or reconnection outflow termination-shocks (Aurass, Vršnak, and Mann, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…It is, in general, accepted that type II bursts at decametric and longer wavelengths are driven by CMEs, bow or flank (Vršnak and Cliver, 2008). At the metric range, on the other hand, they might be also due, apart from CMEs, to flare blasts (Cane and Reames, 1988;Nindos et al, 2011;Magdalenić et al, 2010Magdalenić et al, , 2012 or reconnection outflow termination-shocks (Aurass, Vršnak, and Mann, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Strong associations between type IIs and the shocks ahead of coronal mass ejections (CMEs) have been shown in recent observations, particularly in the interplanetary medium. While CMEs can drive shock waves via a piston mechanism in a plasma [see, e.g., Temmer et al , 2009], very fast coronal shocks may also be blast waves ignited by the pressure pulse of a flare [see, e.g., Nindos et al , 2011]. There is strong evidence that at least some type IIs are generated in electron foreshock regions upstream of the shock waves ahead of CMEs [ Cane et al , 1981; Reiner et al , 1997, 1998; Bale et al , 1999; Reiner and Kaiser , 1999; Pulupa et al , 2010; Cairns , 2011].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that there are a lot of observations of coronal type II bursts, whose radio sources move much faster than associated CMEs (e.g., Magdalenic et al, 2010;Nindos et al, 2011;Bain et al, 2010;Zimovets et al, 2012) and/or EUV waves (e.g., Klassen et al, 2000;Grechnev et al, 2011). There may be various explanations for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Klein et al, 1999;Khan and Aurass, 2002;Dauphin et al, 2006;Bain et al, 2010;Zimovets et al, 2012;Eselevich et al, 2013;Kumar and Innes, 2013) and for samples of a few events (e.g. Gopalswamy and Kundu, 1992;Klassen et al, 1999;Maia et al, 2000;Magdalenic et al, 2010;Ramesh et al, 2010;Nindos et al, 2011). Such type of analysis made by Ramesh et al (2012) at one frequency (109 MHz) for 41 coronal type II radio burst events have shown that all type II bursts were associated with CMEs.…”
Section: Introductionmentioning
confidence: 99%